The Effects of Self-Confidence and Social Support of Parents On Interpersonal Communication of Students - Dian Oktary; Marjohan Marjohan; Syahniar Syahniar (Global Econedu, 2019)
This research is motivated by the problems students face regarding interpersonal communication in school. Self-confidence and parental social support are considered factors that could facilitate this problem. The purpose of this study therefore was to determine the extent to which self-confidence and social support of parents contribute to interpersonal communication. This study uses a descriptive correlational quantitative method and the population assessed were 73 students of SMP N 4 Batusangkarf selected by proportional stratified random sampling technique. The instruments used were self-confidence, parental social support and interpersonal communication. Data was collected using the Likert scale model and analyzed using multiple regression method. The results show a significant (58.1%) relationship between self-confidence and social support of parents with interpersonal communication.